MANIFESTASI KOMUNIKASI PEDAGOGIS DALAM PRESENTASI ILMIAH MAHASISWA UNTUK PENGEMBANGAN MODEL EXPERIENTIAL LEARNING - Umi Kulsum; Yeti Mulyati; Andoyo Sastromiharjo (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
This study aims to describe and analyze the manifestation of pedagogical communication in students’ scientific presentations as a basis for developing an experiential learning model. The study employed a descriptive qualitative design supported by simple quantitative data. The participants consisted of 90 students from three higher education institutions in West Java and lecturers responsible for the related courses. Data were collected through observation, semi-structured interviews, student perception questionnaires, and document analysis, and were analyzed thematically and descriptively. The findings revealed three main points. First, pedagogical communication was present in students’ scientific presentation practices, but it remained dominant in instructional aspects, particularly in clear instructions, activity management, and basic feedback. Second, students’ weaknesses in content elaboration, use of oral scientific language, nonverbal communication, slide design, and ability to answer questions argumentatively were closely related to the underdeveloped dialogic, empathic, and reflective dimensions of pedagogical communication. Third, the findings provide a basis for developing an experiential learning model grounded in pedagogical communication, which emphasizes concrete experience, guided reflection, conceptualization, constructive feedback, and repeated practice as the core of scientific presentation learning.